PDMS lab-on-a-chip fabrication using 3D printed templates - Comina, G (2014)
G. Comina's research stay at Linkoping University has been financed by the Peruvian National Council for Science and Technology (CONCYTEC). This research has been supported by grants from Linkoping Centre for Life Science Technologies (LIST), Sweden, and from the Swedish Research Council (VR).